Perinatal Outcomes in Pregnancy with Preeclampsia and Eclampsia - Rurik Rosa Apriliana; Eny Sendra; Triatmi Andri Yanuarini (STIKes Patria Husada Blitar, 2022)
One of the causes of infant mortality is preeclampsia in pregnancy. The impact of pregnancy with preeclampsia and eclampsia on perinatal outcomes is associated with increased perinatal mortality and morbidity in developing and developed countries. To determine the perinatal condition of pregnancies with preeclampsia and eclampsia in developing and developed countries based on literature studies. This literature study was done to determine the perinatal condition. The external keywords used were perinatal, preeclampsia, eclampsia. The method used literature review research methods and data collection strategies using PEOS obtained from previous research journals that had been collected as many as 22 journals, consisting of 17 international journals and 5 national journals. The variable was perinatal outcomes in pregnancy with preeclampsia and eclampsia. Based on 22 reviewed journals, 19 journals from developing countries and 3 journals from developed countries were found, which stated that the majority of perinatal outcomes were asphyxia. The majority of perinatal outcomes found in developing and developed countries are asphyxia, while other perinatal outcomes found include: low birth weight (LBW), fetal distress, intrauterine fetal death (IUFD), intrauterine growth restrictions (IUGR), and perinatal mortality.